Association Between Mother Factors With Prelacteal Feeding Practice To Newborn In Working Area Of Air Dingin Primary Health Center 2017 - Yunita Chairani; Yuniar Lestari (Universitas Andalas, 2017)
The maintenance of infant health can be done by early and exclusive breastfeeding. However, exclusive breastfeeding has not been achieved. This may be due to the administration of prelakteal foods. Prelacteal feeding practice define as administration of food/drink despite of breastmilk without indication to newborn during the first three days without any medical indication. The purpose of this study is to determine the association between maternal factors with prelakteal feeding to newborns in the working area of Air Dingin Primary Health Center. This study was an analytical study with cross sectional design with a sample of mothers who have babies aged 0-12 months in the working area of Air Dingin Primary Health Center. This study was conducted from November 2016 to October 2017. Data will analyze using chi square analysis (p <0.05). A total of 63% of mothers administrated prelakteal foods. The result revealed p-value between prelakteal feeding and maternal knowledge (p = 0,03), parity (0,037) and mother’s job status (p = 0,771). There was a significant relationship between maternal knowledge and parity with prelakteal feeding. It is necessary to provide information to the mother by health workers and to increase mother awareness to get information from KIA book. As well as a concern on primipara mothers.